Designing a Structural-interpretive Model of Information Disclosure Factors related to Sustainable Development Accounting - Mohammadreza Abbasi Astamal; Mehdi Zeynali (Iranian Journal of Accounting, Auditing & Finance, 2021)
The current study aims to design a structural-interpretive model for disclosing information related to sustainable development accounting in 2020-2021. Qualitative data were obtained through the study of research and credible sources in the field of sustainable development accounting with content analysis approach and in the form of 4 dimensions (environmental, social factors, economic factors and leadership) in the form of 12 variables using fuzzy Delphi method and matrix questionnaire to determine Pairs of variables were compiled and provided to experts. The study's statistical population includes 25 experts in sustainable development accounting. The data obtained from the questionnaire were analysed using a structural interpretive model and drawn at six levels in an interactive network. Also, these variables' influence and degree of dependence on each other in the influence-dependence power matrix were examined. According to the output of the interpretive structural model, the variables of products and services provided and corporate governance are level one or the most basic elements of the model and the variables of strategic approach to the environment and promotion of moral awareness as the level six variable and the most influential model variable. This study indicates that by disclosing information related to sustainable development accounting factors, managers and policymakers can provide more transparent information to stakeholders by formulating appropriate policies and standards in sustainable development accounting, which leads to social welfare and environmental protection. For future generations, capital market growth and increasing the quality of reporting will ultimately lead to the sustainable performance of companies in the long run.